2021
DOI: 10.3389/fphar.2021.726669
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of CYP3A and Drug Transporters Activity in Healthy Young, Healthy Elderly and Chronic Kidney Disease Elderly Patients by a Microdose Cocktail Approach

Abstract: Background: Ageing and chronic kidney disease (CKD) affect pharmacokinetic (PK) parameters. Since mechanisms are related and remain unclear, cytochrome P450 (CYP) 3A and drug transporter activities were investigated in the elderly with or without CKD and compared to healthy adults using a microdose cocktail.Methods: Healthy young participants (n = 20), healthy elderly participants (n = 16) and elderly patients with CKD (n = 17) received, in study period 1, a single dose of microdose cocktail probe containing 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Kirwan et al (2009) reported increased plasma concentrations of midazolam in patients with AKI compared to those in patients with normal kidney function (Kirwan et al, 2009). On the other hand, clinical pharmacokinetic change of midazolam in CKD patients compared with healthy control subjects was not observed or slightly reduced according to several clinical investigations (Nolin et al, 2009;Thomson et al, 2015;Rattanacheeworn et…”
Section: Mechanisms Underlying the Functional Changes In Hepatic Prot...mentioning
confidence: 99%
“…Kirwan et al (2009) reported increased plasma concentrations of midazolam in patients with AKI compared to those in patients with normal kidney function (Kirwan et al, 2009). On the other hand, clinical pharmacokinetic change of midazolam in CKD patients compared with healthy control subjects was not observed or slightly reduced according to several clinical investigations (Nolin et al, 2009;Thomson et al, 2015;Rattanacheeworn et…”
Section: Mechanisms Underlying the Functional Changes In Hepatic Prot...mentioning
confidence: 99%
“… DDI prediction between DABE and CYP3A/P-gp inhibitors: ITZ (A) , RF (B,C) , CTC (D) , VP concomitantly (E) , and VP 1 h before DABE (F) from Prueksaritanont et al (2017) , Rattanacheeworn et al (2021) , Gouin-Thibault et al (2017) , and Hartter et al (2013) , respectively. Blue circles and blue lines represent the observed and simulated DAB levels for the control phase, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that another two clinical studies showed less impact of renal impairment on rosuvastatin exposure 13,36 . Rattanacheeworn et al 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that another two clinical studies showed less impact of renal impairment on rosuvastatin exposure. 13,36 Rattanacheeworn et al 36 suggested aging rather than CKD disease effect plays a more important role in rosuvastatin PK. However, other studies reported no association between aging and rosuvastatin exposure.…”
Section: Discussionmentioning
confidence: 99%